PROBLEMS OF LINGUOCULTURAL CONCEPTS IN TRANSLATION - Qurbonova Mohichehra Irgashevna (Galaxy International Interdisciplinary Research Journal, 2021)
Dear reader, this article deals with one of the most difficult topics today linguistics, linguoculturology. In linguistics, thephrase linguoculture is used in a broad sense. Linguoculturology studies language as a phenomenon of culture, a carrier of culture. Culture is created by a person who uses language. The object oflinguoculturology is at the intersection of linguistics and a number of fundamental disciplines suchas culturology, ethnography and psycholinguistics. The term linguoculturology was originally used during the study of phraseological units under the direction of V.N. Telia. In his view, "Linguoculturology is the study of the human being, more precisely, the integration of personality and cultural factors." This article provides information on Translation Skills, what qualities a translator should have, and what to look for.